Pheophorbide a from Capsosiphon fulvescens Inhibits Advanced Glycation End Products Mediated Endothelial Dysfunction - Hong, Chung-Oui; Nam, Mi-Hyun; Oh, Ji-Sun; Lee, Jin-Won; Kim, Cheong-Tae; Park, Kwon-Woo; Lee, Dong-Ho; Lee, Kwang-Won (Planta Medica, 2016)
During hyperglycemia, the first step toward the formation of advanced glycation end products is the nonenzymatic glycation between the carbonyl group of a sugar and the primary amino group of a protein. Advanced glycation end products are then produced through more complex reactions. Reactive oxygen species derived from advanced glycation end products may play a key role in inflammation of the endothelium, leading to the complications seen in diabetes. Glycolaldehyde-induced advanced glycation end products have been reported to express proinflammatory cytokines, such as tumor necrosis factor-α and interleukin-1β. This study focused on Capsosiphon fulvescens, a Capsosiphonaceae type of green algae that has shown potential as a functional food material. Pheophorbide a, an anti-glycation compound, was isolated from C. fulvescens by extraction using a mixture of ethanol and water, followed by column fractionation of the resulting extract. The compound separated from C. fulvescens was identified by means of high-performance liquid chromatography combined with mass spectrometry. Pheophorbide a showed scavenging activity of the intracellular reactive oxygen species as well as monocyte adhesiveness inhibitory activity on the human myelomonocytic cell line (THP-1) and human umbilical vein endothelial cells cocultivation system. The mRNA levels of inflammation-related genes such as monocyte chemoattractant protein-1 and interleukin-6 were significantly decreased by pheophorbide a, and advanced glycation end products-stimulated tumor necrosis factor-α and interleukin-1β were downregulated as well. These results indicate that pheophorbide a has significant reactive oxygen species-scavenging activity, monocyte adhesive inhibitory activity, and downregulatory activity of cytokines related to inflammation affecting the endothelium. Pheophorbide a could therefore be a promising candidate for modulating endothelial cell dysfunction.
Keywords: Capsosiphon fulvescens; Capsosiphonaceae; pheophorbide a; advanced glycation end product; proinflammatory cytokine; endothelial cell dysfunction